The image of dog in Kazakh traditions and folk beliefs - Argynbayev, Yerzhan (Turkic Studies Journal, 2024)
The dog, one of the first domesticated animals, played an important role in all epochs of history and found its place in every culture. Among the Kazakhs, the dog was considered one of the seven treasures, such as a faithful friend of man, a keeper of the house, a guard of four types of domestic animals, a shepherd and a hunter. In addition, the dog has become a part of social and cultural life and takes an important place in the traditions, beliefs, art and vocabulary of the Kazakh people. This study aims to define the origins of positive and negative attitudes towards dogs in Kazakh society and to identify their basic expressions in traditions and folk beliefs. In this article Kazakh traditions and folk beliefs are carefully considered, as well as a number of crafts in which superstitions and customs are associated with the concept of a dog. The results of this study show that in Kazakh culture a dog is not only a pet, but also a cultural symbol and mythological figure. Therefore, dogs have both positive and negative meanings in the collective consciousness of Kazakh society, as well as practical, ritual and mythological significance.